Peran AI Dalam Pengembangan Layanan Perbankan Berbasis E-Commerce - Abidzar Fikri Simamora; Putri Chairunnisa Pane; Sherin Aulia Putri; Nurbaiti . (CV. ITTC INDONESIA, 2025)
This study examines the role of artificial intelligence in developing e-commerce-based banking services in Indonesia through a qualitative approach. The research aims to explore the implementation of AI technology in banking operations, identify benefits and challenges faced, and understand its impact on customer service quality. Using qualitative descriptive methodology with literature review and document analysis, data was collected from scientific journals, national seminar proceedings, and relevant documentation published between 2021-2025. Data analysis employed thematic content analysis to identify key patterns and themes. Findings reveal that AI implementation through chatbots, fraud detection systems, and personalized recommendation engines significantly enhances banking service efficiency and customer experience in e-commerce platforms. Key themes emerged include operational transformation, service quality improvement, regulatory challenges, and data security concerns. The study contributes to understanding AI integration dynamics in digital banking services, particularly in supporting inclusive and sustainable Islamic economic growth. Recommendations include strengthening cybersecurity infrastructure, developing comprehensive regulations through multi-stakeholder collaboration, and enhancing financial literacy programs regarding AI-based banking services.